Pengaruh Authentic Leadership terhadap Customer-Oriented Organizational Citizenship Behavior dan Service Recovery Performance melalui Job Crafting dan HR Flexibility - Yogatama, Aziz; Nugrohoseno, Dwiarko (Jurnal Ilmu Manajemen, 2021)
This study aims to determine and explain the effect of authentic leadership on service recovery performance and customer-oriented organizational citizenship behavior (Co-OCB) through job crafting and HR flexibility at a telecommunication company, PT. Telkom Indonesia in Surabaya region. This research is causality research with a quantitative approach—the sampling technique used non-probability sampling, namely purposive sampling. Statistical analysis used Partial Least Square (PLS) with SmartPLS 3.0 software. This study explains that authentic leadership does not affect customer-oriented OCB and service recovery performance. Then Co-OCB does not have any effect in mediating the relationship between authentic leadership and service recovery performance. However, job crafting has been shown to mediate the relationship between authentic leadership and Co-OCB and service recovery performance. HR flexibility is not proven in moderating the relationship between authentic leadership and job crafting in the context of high flexibility.